Performance evaluation of porous asphalt mixture reinforced by lignin fiber - Fatin Fahira Nisha, Mohd Fazilah; Khairil Azman, Masri; Al-Attab, Ammar; Putra Jaya, Ramadhansyah (IOP Science, 2025)
This study aims to investigate the performance evaluation of porous asphalt (PA) mixture reinforced by lignin fiber. A kind of pavement called porous asphalt is made to let water percolate through its surface, minimising runoff and enhancing water management. Because of the unique combination of aggregates and asphalt used in its construction, water can percolate through and be absorbed into the ground below. However, there is always room for improvement in terms of enhancing its mechanical properties and overall performance. In this research, lignin fiber is incorporated into Porous Asphalt to evaluate their influence on key performance indicators such as rutting resistance, fatigue life, cracking, and mechanical strength. The study includes laboratory tests and performance assessments to compare the modified PA with conventional PA. To achieve the research objectives, various proportions of lignin fiber additives are introduced into the PA mix design (0%, 1%, 2%, 3%, 4%). The modified asphalt mixtures are then prepared and subjected to comprehensive laboratory tests, including Marshall stability, Indirect tensile strength, Binder drain down test, LA abrasion loss, Softening point and Penetration test. The performance evaluation also involves rutting and fatigue tests to assess the resistance of the modified mixtures to permanent deformation and fatigue cracking under simulated traffic loading conditions. The results obtained from the experimental investigations are analyzed and compared with the performance characteristics of conventional LF. In conclusion, the addition of 2-3% of LF additives enhanced the performance of PA in terms of rutting resistance, fatigue life, moisture susceptibility, and mechanical strength.